Calcitonin gene-related peptide (CGRP) receptor antagonists for the acute treatment of migraines in adults - Eric R Ocheretyaner; Maria Kofman; Elaena Quattrocchi (BioExcel Publishing Ltd, 2022)
Migraine headaches are widespread, debilitating and considered a main cause of disability worldwide. Symptoms of migraines include unilateral, pulsating pain that can last for hours to days, frequently associated with photophobia and phonophobia, nausea, or vomiting, and often aggravated by physical activity. The Canadian Headache Society and American Headache Society guidelines suggest strong evidence of the efficacy of triptans, acetaminophen, aspirin, diclofenac sodium, naproxen and ibuprofen for the acute treatment of migraines. The use of calcitonin gene-related peptide (CGRP) antagonists for the treatment and prevention of migraines has been gaining utilization since the approval of the first agent in this class in 2018. There are increasing available options for the acute treatment of migraines. The purpose of this article is to provide a narrative review of the pharmacological and clinical characteristics of ubrogepant and rimegepant and to discuss their implications for use.